Effect of in-vivo hepatitis B viral load suppression after interferon exposure on natural killer and T-cell responsiveness. (23rd February 2017) - Gill, Upkar S; Peppa, Dimitra; Micco, Lorenzo; Singh, Harsimran D; Le Bert, Nina; Rivino, Laura; Kunasegaran, Kamini; Tan, Damien; Bertoletti, Antonio; Maini, Mala K; Kennedy, Patrick T F
Abstract: Background: There is a pressing need for new treatment strategies in chronic hepatitis B. Natural killer (NK) cells are important antiviral effectors, and are potently expanded with peginterferon alfa in chronic hepatitis B. Robust antiviral T-cell responses are crucial for resolution of this disease and can be expanded with nucleos(t)ide analogues (NAs). We assessed whether changes in the NK and T-cell pool would be altered when patients are primed with peginterferon alfa and whether these changes are modulated upon switching to sequential NAs. Methods: Peripheral blood mononuclear cells from 52 patients were analysed. 33 underwent a course of peginterferon alfa and were sampled longitudinally; 24 of them progressed to sequential NAs. 19 patients receiving de-novo NA therapy were analysed for comparison. NK cell subsets and global T cells were analysed by multicolour flow cytometry, and hepatitis B virus (HBV)-specific T cells were analysed by enzyme-linked immunospot assay and correlated with treatment outcomes. Findings: There was cumulative expansion of CD56 bright NK cells driven by peginterferon alfa, which was maintained at higher than baseline concentrations throughout subsequent sequential NAs (p=0·0039). The expansion in proliferating, functional NK cells was more pronounced after sequential NAs compared with de-novo NAs. Patients treated with peginterferon alfa progressing to sequential NAs expressed higher levels of CD69, CD62L, and CXCR3 (implicated in antifibrogenesis) than did patients on de-novo therapy. Reduction in circulating HBsAg concentrations was only achieved in patients with enhancement of NK cell interferon γ and cytotoxicity. Partial recovery of HBV-specific T cells was seen during sequential NAs after peginterferon alfa cessation. Interestingly, no difference in the magnitude of HBV-specific T-cell responses was seen in patients on sequential NAs compared with de novo NAs. Interpretation: Peginterferon alfa priming expands a population of functional NK cells, with altered responsiveness to subsequent viral suppression by NAs. We have previously reported that NK cells can delete HBV-specific T cells, but our findings here suggest that the peginterferon alfa expanded NK cell pool does not exhibit this negative effect. We are investigating whether peginterferon alfa is able to protect T cells from NK cell attack, as demonstrated in a mouse model by other investigators. Funding: Wellcome Trust, Barts and The London Charity, National Medical Research Council Singapore.